PELATIHAN PENGOPERASIAN PLATFORM PEMBELAJARAN ONLINE DALAM MASA PANDEMI COVID-19 BAGI ANAK-ANAK DESA BATUAJI KECAMATAN RINGINREJO KABUPATEN KEDIRI - Aprilia, Riska; Damayanti, Tri Intan; Sari, Ninik Yustina; Putri, Lifa Rosiana (Jurnal Praksis dan Dedikasi Sosial, 2023)
TRAINING OF ONLINE LEARNING PLATFORM OPERATIONALPROCEDURE FOR CHILDREN IN BATUAJI, KEDIRI, DURING THE COVID19 PANDEMIC Online learning is commonly carried out. Especially during the COVID-19 pandemic, onlinelearning is implemented to prevent the extensive spread of COVID-19. However, during itsimplementation, online learning faces a number of hindrances, such as the student’s inability tooperate the online learning platform, which reflects the unpreparedness for online learning.Therefore, we conducted training on online learning platform operations for children from Batuaji,Kediri, Indonesia. This training aimed to help students operate a number of online learningplatforms, such as google classroom, zoom, google meet, edmodo, quizizzz, and whatsapp. Theelementary school and junior high school-age children participated in this training. The trainingprocess was initiated by introduction, short material delivery related to the online learningplatforms, quizzes, and evaluation. This training is helpful for the participants, as reflected by theirgreat enthusiasm during the training activities and great understanding of online learningplatforms’ operation procedures after attending the training. Pembelajaran online merupakan kegiatan yang sedang dilaksanakan selama pandemi COVID19. Hal ini dilakukan guna menghindari penyebaran COVID-19 yang semakin meluas. Sesuaidengan praktiknya kegiatan pembelajaran online menemui beberapa hambatan, salah satunyayakni banyaknya anak-anak yang belum menguasai penggunaan platform pembelajaran onlinesehingga menimbulkan ketidaksiapan dalam pembelajaran online. Oleh karena itu, kegiatan inibertujuan untuk memberikan solusi dengan mengadakan pelatihan pengoperasian platformpembelajaran online dalam masa pandemi COVID-19 bagi anak-anak di Desa Batuaji KecamatanRinginrejo Kabupaten Kediri guna membantu agar mereka memahami cara mengoperasikanbeberapa platform pembelajaran online seperti google classroom, zoom, google meet, edmodo,quizizz dan whatsapp. Pelatihan ini dilakukan bagi anak-anak SD dan SMP dengan rangkaiankegiatannya diawali perkenalan, pemaparan materi tentang platform pembelajaran online secarasingkat, praktik kuis, dan evaluasi pelatihan. Hasil pelatihan ini sangat bermanfaat, bahkansemua peserta pelatihan sangat antusias selama kegiatan berlangsung serta mereka jugamemahami beberapa aplikasi yang baru mereka kenal selama pelatihan.